Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1111/j.1600-051x.1989.tb02326.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of root debridement in molar and non‐molar teeth A 2‐year follow‐up

Abstract: 12 patients were studied longitudinally to monitor the effects of basic periodontal therapy in molar and non‐molar teeth. Periodontal sites were grouped into molar furcation sites, molar fiat‐surface sites and non‐molar sites. Clinical measurements were taken at baseline and directly followed by full mouth root debridement. Subsequently, measurements were taken every 3rd month until 24 months. At each of these appointments, the patients were monitored for their oral hygiene performance and given supragingival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
0
9

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(123 citation statements)
references
References 40 publications
6
108
0
9
Order By: Relevance
“…7 For example, increased periodontal probing depth (PPD), clinical attachment loss (CAL) and a higher percentage of missing teeth are observed for M. [8][9][10][11] In this scenario, the initial observations of Nordland et al 12 and Loos et al 13 are particularly important. They compared free surfaces of M and non-molars (NM) with those having furcation involvement and observed that the worst condition was always associated with M. Nevertheless, most studies have not evaluated the response of different teeth to systematic periodontal intervention.…”
Section: Introductionmentioning
confidence: 99%
“…7 For example, increased periodontal probing depth (PPD), clinical attachment loss (CAL) and a higher percentage of missing teeth are observed for M. [8][9][10][11] In this scenario, the initial observations of Nordland et al 12 and Loos et al 13 are particularly important. They compared free surfaces of M and non-molars (NM) with those having furcation involvement and observed that the worst condition was always associated with M. Nevertheless, most studies have not evaluated the response of different teeth to systematic periodontal intervention.…”
Section: Introductionmentioning
confidence: 99%
“…7 Ara yüzlerin etkin bir şekilde temizlenememesi, sondalamada kanama ve sondalama derinliklerinde artış ile periodontal hastalığın oluşmasına zemin hazırlamaktadır. 8 Bu sebeple hekimler, bireyin ihtiyacına uygun temizleme araçları ve bu araçların kullanım teknikleri hakkında literatürdeki kanıta dayalı veriler ışığında hastalarını bilgilendirmekle yükümlüdür. 9 Yalnızca diş fırçalama ile dişler üzerinde biriken dental plak biyofilm tabakasının %65-70'inin uzaklaştırılabildiği bilinmektedir.…”
Section: Discussionunclassified
“…Bu bulgular ışığında, derin cep bölgelerinde sığ cep bölgeleri-ne kıyasla ve çok köklü dişlerdeki cep bölgelerinde tek kök-lü dişlerdeki cep bölgelerine kıyasla rezidüel cep kalma oranının daha yüksek olduğu görülmektedir. Bu durum derin periodontal ceplerde el ve ultrasonik aletlerin yetersizliği ve cep tabanına ulaşılabilirliğin zorluğu, çok köklü dişlerde furkasyon bölgelerinin ve kök konkavitelerinin varlığı, bu diş-lerin daha distalde konumlanmaları, hastanın ağız açıklığı-nın ve yanak esnekliğinin azlığı gibi tedavi başarısını olumsuz etkileyen faktörlerin varlığı ile açıklanabilir (37)(38)(39)(40). Bu sebeple, periodontal dokuların muayenesi sırasında SD ölçümleri altı bölgeden kaydedilmeli, çok köklü dişlerin anatomik ve morfolojik özellikleri göz önünde bulundurulmalı ve çok köklü dişlerde özel furkasyon sondaları kullanıl-malıdır.…”
Section: Tartişma Ve Sonuçunclassified